Development of Life Based Learning E-Modules to Improve Students' Critical Thinking Skills - Nurdyansyah, Nurdyansyah; Arifin, Moch. Bahak Udin By; Cemerlang, Dipta Arimbi Hariba; Rais, Pandi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to develop and analyze the feasibility, practicality, and effectiveness of e-modules based on life-based learning for improving students' critical thinking skills. The research employs the Research and Development (R&D) method with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Data collection techniques included questionnaires, document checklists, and tests. The results indicated that material expert validation yielded a value of 3.83 (95.8%), categorizing it as very valid, while media expert validation resulted in a value of 3.70 (92.5%), also classified as very valid. Linguist validation achieved a value of 3.85 (96.4%), falling into the very valid category. The practicality test of the product scored 98.4%, indicating it is very interesting and practical. The t-test results revealed a significant increase in critical thinking skills after using e-modules based on life-based learning. Specifically, the pre-test average score was 64.25, and the post-test average score was 88.41. The t-test p-value was 0.00 (less than 0.05), leading to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). This shows that: 1) the e-module is practical, interesting, and effective as a learning tool for enhancing students' critical thinking skills, and 2) there is a significant improvement in students' critical thinking skills.